(untitled) (World Science, 2023)
The nature of medicinal products of plant origin is determined by the content of various active components, which makes it possible to use them as therapeutic excipients in traditional medicine. The objects of the research were the roots and the ground part of butcher’s broom wild-growing in Georgia, in the active phase of vegetation: root - in November, the ground part (stem and leaves) in May. The 70% and 40% ethanol alcoholic extracts from root and herbs were prepared, 26.6 - 60.4 mg/g of total phenols were found in all four extracts; the content of flavonoids was 9.2 - 21.2 mg/g and the antioxidant activity was evaluated by the DPPH method at 24.3 - 68.2%.